2018
DOI: 10.1002/ange.201806849
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Species in the Reversible Activation of H2

Abstract: MP(tBu) 2 (M = Li, Na, K), KH and KN(SiMe 3 ) 2 are shown to activate HD reversibly.Inthe case of MP(tBu) 2 this leads to isotopic scrambling and the formation of H 2 ,D 2 , H(D)P(tBu) 2 and MH(D) in C 6 D 6 .Intoluene,KP(tBu) 2 reacts with H 2 but also leads to isotopic scrambling into the methyl groups of the solvent toluene.D FT calculations reveal that these systems effect H 2 activation via cooperative interactions with the Lewis acidic alkali metal and the basic phosphorus, carbanion, or hydride centres,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…Therefore, 4a was reacted in the first step with CS 2 to form the bulky potassium phosphanyl dithioformate 10 . The reaction behavior of 4a toward CS 2 is in accordance with previously reported reactions of bulky group 1 phosphides with small molecules. …”
Section: Resultssupporting
confidence: 90%
“…Therefore, 4a was reacted in the first step with CS 2 to form the bulky potassium phosphanyl dithioformate 10 . The reaction behavior of 4a toward CS 2 is in accordance with previously reported reactions of bulky group 1 phosphides with small molecules. …”
Section: Resultssupporting
confidence: 90%
“…(4)], did take place in presence of CsHMDS, suggesting the existence of the carbanion or hydride intermediates. On the basis of these observations and former reports, [16, 18] we proposed a plausible process as shown in Scheme 2B. The cesium amide could undergo the kinetic deprotonative process to produce benzyl anion as a thermodynamically uphill intermediate ( 1 ) at very low concentrations.…”
Section: Methodssupporting
confidence: 55%
“…The poor activity of base catalysts towards T 2 (H 2 ) remains a significant challenge for high‐specific‐activity tritiation. In 2018, Stephan and co‐workers revealed that alkali metal species can mimic frustrated Lewis pair (FLP) behavior for reversible activation of H 2 , and specifically KH was shown to deuterate benzylic C−H bonds of toluene in presence of D 2 gas, albeit with only 15 % deuterium incorporation (Scheme 1C1) [16] . Furthermore, Harder and co‐workers later found the heavier alkaline earth metal amides to be active catalysts for HIE of arenes with D 2 gas, but showing moderate level of isotope incorporation at benzylic C−H bonds (Scheme 1C2) [17] .…”
Section: Methodsmentioning
confidence: 99%